Office or Officeholder? Regime Deinstitutionalization and Sources of Individual Political Influence. (4th June 2014) - Baturo, Alexander; Elkink, Johan A.
Abstract : How to separate the office from the officeholder is one of the most difficult questions in the empirical study of institutions and leadership. We argue that provided there is an indicator for the overall individual influence among members of the political elite and there is sufficient variability among individuals taking the same office, being promoted and demoted into different offices over time, we can separate latent individual and institutional components of influence at an aggregate, regime level. Our latent variable model thus provides a new tool to measure the degree of regime deinstitutionalization. Using expert surveys that assess the ranking of the top political actors in Russia from 1994 to 2011 and restricting personal effects to those that are constant over time, we find that on average office dominates individual by the order of two. We discuss regime deinstitutionalization in comparative perspective, demonstrate the generalizability by analyzing Ukraine, and account for patronage networks.